The Influence of Adverse Childhood Experiences in Pain Management: Mechanisms, Processes, and Trauma-Informed Care - Tidmarsh, Lydia V.; Harrison, Richard; Ravindran, Deepak; Matthews, Samantha L.; Finlay, Katherine A. (Frontiers in Pain Research, 2022)
Adverse childhood experiences (ACEs) increase the likelihood of reduced physical and psychological health in adulthood. Though understanding and psychological management of traumatic experiences is growing, the empirical exploration of ACEs and physical clinical outcomes remains under-represented and under-explored. This topical review aimed to highlight the role of ACEs in the experience of chronic pain, pain management services and clinical decision making by: (1) providing an overview of the relationship between ACEs and chronic pain; (2) identifying biopsychosocial mechanisms through which ACEs may increase risk of persistent pain; (3) highlighting the impact of ACEs on patient adherence and completion of pain management treatment; and (4) providing practical clinical implications for pain management. Review findings demonstrated that in chronic pain, ACEs are associated with increased pain complications, pain catastrophizing and depression and the combination of these factors further heightens the risk of early treatment attrition. The pervasive detrimental impacts of the COVID-19 pandemic on ACEs and their cyclical effects on pain are discussed in the context of psychological decline during long treatment waitlists. The review highlights how people with pain can be further supported in pain services by maintaining trauma-informed practices and acknowledging the impact of ACEs on chronic pain and detrimental health outcomes. Clinicians who are ACE-informed have the potential to minimize the negative influence of ACEs on treatment outcomes, ultimately optimizing the impact of pain management services.